High quality cassava flour, promising raw material for bread, biscuit and pastry industries: lessons from a pilot study in Madagascar - Ranaivoson, R.L.; Abass, A.; Razafindrazaka, A.; Randrianarivelo, R.; Rakotomalala, V.; Antasoa, R.; Rasoaharaona, J. (International Society for Tropical Root Crops, 2012)
Cassava is the second most important staple crop in Madagascar after rice, in term of production volume and area cultivated. Traditional cassava processing techniques are rudimentary and provide insignificant market opportunities to the smallholder cassava farmers. On the other hand, market survey showed that the high price of wheat flour in the retail market high, 0.9 to 1.08 US$ per kg, and bakers desired a substitute raw material. The potential market demand for High Quality Cassava Flour (HQCF) by local bakeries, a biscuit factory, and the caterers in Antananarivo was about 9,400 tons a year. A project to vertically integrate the cassava sector through the processing and supply of HQCF to bakers was implemented in Madagascar from 2003 to 2007. The HQCF technology was introduced at pilot-scale to farmers in Ambatomanoina locality of Madagascar. The technology introduction was accompanied with training of farmers in all aspects of business enterprise management. The pilot farmers produced 24.3 tons of high quality cassava flour a month from the first year. Annual cost of production for HQCF was estimated at US$ 17,328. Profitability analysis revealed profit about US$ 18,783.